2019
DOI: 10.1590/0037-8682-0156-2019
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Spotted Fever Prevention through a Nonlethal Capybara Population Control Strategy

Abstract: Introduction: Brazilian spotted fever (BSF), a lethal tick-borne Rickettsioses (2000-2018 >600 human deaths) involving synanthropic capybara as host. Methods: We introduced an alternative to mitigate human-capybara conflicts and epidemiologic concerns of BSF. Complex aspects like transmission dynamics, risk areas, host mobility, and birth rate control, were considered to develop a prevention strategy using an anti-GnRH vaccine. Results: The propositioned immunocontraceptive potentially remove and prevent the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In this sense, the re‐establishment of the connectivity among native natural areas in human‐modified landscapes, mediated by ecological restoration, might help reinstate at least some of the natural balance by providing access routes to predators (pumas, caimans), for example. Another possibility to reduce the number of individuals, in particular cases, is to perform contraceptive methods such as vasectomy in males or tubal ligation in females, or through immunocontraception, a less invasive method (Rosenfield et al, 2019). All the results presented here, together with the behavioral plasticity of the species, help in explaining the resilience of the capybara in surviving and thriving in both favorable and unfavorable conditions along with its distribution, in natural or human‐modified environments.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the re‐establishment of the connectivity among native natural areas in human‐modified landscapes, mediated by ecological restoration, might help reinstate at least some of the natural balance by providing access routes to predators (pumas, caimans), for example. Another possibility to reduce the number of individuals, in particular cases, is to perform contraceptive methods such as vasectomy in males or tubal ligation in females, or through immunocontraception, a less invasive method (Rosenfield et al, 2019). All the results presented here, together with the behavioral plasticity of the species, help in explaining the resilience of the capybara in surviving and thriving in both favorable and unfavorable conditions along with its distribution, in natural or human‐modified environments.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocontraceptive vaccines have been proposed as an effective contraceptive strategy for male capybaras, preserving the alpha male's social behavior ( Rosenfield & Pizzutto, 2019 ), with the benefit of being less invasive ( Rosenfield et al, 2019a ) and also being a strategy for BSF control ( Rosenfield et al, 2019c ).…”
Section: Discussionmentioning
confidence: 99%
“…Associating management practices for capybaras in areas that are endemic for BSF with quality of life for this species is challenging, since these practices must be effective given the risk imposed to public health. The stochastic model proposed by POLO et al (2017) andROSENFIELD et al (2019b) demonstrated how strategies to control and prevent the transmission of infectious diseases by vectors can be focused on management practices towards amplifying hosts. This showed that actions should be directed towards the capybaras and that important effort has been underway in the planning of reproductive control programs.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies to decrease capybara populations through contraceptive methods reduce their capacity to carry and transport ticks, and mostly important, reduce the number of newborns that could act as amplifying hosts through their primary infection by R. rickettsii (POLO et al, 2017;ROSENFIELD et al, 2019b;ROSENFIELD et al, 2019c). Hence, any method that decreases capybara reproduction in a BSF-endemic area can be an effective alternative to control the disease.…”
Section: Microbiologymentioning
confidence: 99%